Central or peripheral delivery of an adenosine A1 receptor agonist improves mechanical allodynia in a mouse model of painful diabetic neuropathy. (29th January 2015) - Katz, N.K.; Ryals, J.M.; Wright, D.E.
Highlights: Male A/J mice develop mechanical allodynia following induction of diabetes. Diabetes decreases AMP hydrolysis in the DRG in small- and medium-diameter neurons. Central delivery of A1 R agonists improves mechanical allodynia in diabetic mice. Peripheral delivery of an A1 R-specific agonist improves mechanical allodynia. Abstract: Diabetic peripheral neuropathy is a common complication of diabetes mellitus, and a significant proportion of individuals suffer debilitating pain that significantly affects their quality of life. Unfortunately, symptomatic treatment options have limited efficacy, and often carry significant risk of systemic adverse effects. Activation of the adenosine A1 receptor (A1 R) by the analgesic small molecule adenosine has been shown to have antinociceptive benefits in models of inflammatory and neuropathic pain. The current study used a mouse model of painful diabetic neuropathy to determine the effect of diabetes on endogenous adenosine production, and if central or peripheral delivery of adenosine receptor agonists could alleviate signs of mechanical allodynia in diabetic mice. Diabetes was induced using streptozocin in male A/J mice. Mechanical withdrawal thresholds were measured weekly to characterize neuropathy phenotype. Hydrolysis of AMP into adenosine by ectonucleotidases was determined in the dorsal root ganglia (DRG) and spinal cord at 8 weeks post-induction of diabetes. AMP, adenosine and the specific A1 R agonist, N 6 -cyclopentyladenosine (CPA), were administered both centrally (intrathecal) and peripherally (intraplantar) to determine the effect of activation of adenosine receptors on mechanical allodynia in diabetic mice. Eight weeks post-induction, diabetic mice displayed significantly decreased hydrolysis of extracellular AMP in the DRG; at this same time, diabetic mice displayed significantly decreased mechanical withdrawal thresholds compared to nondiabetic controls. Central delivery AMP, adenosine and CPA significantly improved mechanical withdrawal thresholds in diabetic mice. Surprisingly, peripheral delivery of CPA also improved mechanical allodynia in diabetic mice. This study provides new evidence that diabetes significantly affects endogenous AMP hydrolysis, suggesting that altered adenosine production could contribute to the development of painful diabetic neuropathy. Moreover, central and peripheral activation of A1 R significantly improved mechanical sensitivity, warranting further investigation into this important antinociceptive pathway as a novel therapeutic option for the treatment of painful diabetic neuropathy.